2007
DOI: 10.1093/ps/86.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Grape Pomace and Vitamin E on Growth Performance, Nutrient Digestibility, and Susceptibility to Meat Lipid Oxidation in Chickens

Abstract: Grape pomace (GP) is a source of polyphenols with powerful antioxidant capacity. An experiment was conducted to investigate the effect of inclusion of GP at levels of 5, 15, and 30 g/kg and alpha-tocopheryl acetate (200 mg/kg) in a corn-soybean basal diet on growth performance, protein and amino acid digestibilities; antioxidant activity of diet, serum and excreta, lipid oxidation of breast and thigh meats during refrigerated storage, and liver vitamin E concentration. Growth performance and protein and amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
163
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(196 citation statements)
references
References 50 publications
22
163
2
9
Order By: Relevance
“…The protective effects of grape pomace and grape seed extracts on growing chickens were studied by a group of researchers from Spain and the results were published in a series of papers from the same department (Goñiet al, 2007;Brenes et al, 2008;Viveros et al, 2011). The use of smaller quantities of grape pomace of 5 g/kg and 15 g/kg did not improve growth performance of the chickens, the values obtained being very close to the group that did not receive feed grape pomace (Goñi et al, 2007;Brenes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of grape pomace and grape seed extracts on growing chickens were studied by a group of researchers from Spain and the results were published in a series of papers from the same department (Goñiet al, 2007;Brenes et al, 2008;Viveros et al, 2011). The use of smaller quantities of grape pomace of 5 g/kg and 15 g/kg did not improve growth performance of the chickens, the values obtained being very close to the group that did not receive feed grape pomace (Goñi et al, 2007;Brenes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol content of diets is difficult to establish due to variations in polyphenol solubility, which can produce significant errors (Saura-Calixto et al 2007). The commonly used colorimetric method of the Folin Ciocalteu (FC) reaction forms a blue chromophore constituted by a phosphotungstic-phosphomolybdenum complex, where the maximum absorption of the chromophores depends on the alkaline solution and the concentration of phenolic compounds (Singleton et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In one experimen, the dietary inclusion of grape pomace as a source of polyphenols with powerful antioxidant capacity enhanced the antioxidant status of the diet, blood serum and excreta in broiler chickens, and increased lipid oxidation rates in meat (Goni et al 2007). Beneficial effects of fruit pomaces on blood parameters were noted in piglets fed diets supplemented with apple pomace (Sehm et al 2011) and in rats fed diets with polyphenol-rich strawberry pomace (Jaroslawska et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant effect of grape seed extract when added directly to raw or cooked pork has been confirmed by CARPENTER et al (2007). Also, the inclusion of concentrated grape pomace in the diet of chickens reduced lipid oxidation of raw or cooked meat (GOÑI et al, 2007;BRENES et al, 2008;SÁYAGO-AYERDI et al, 2009), but the same effect was not observed when grape seed extract was given to pigs (O'GRADY et al, 2008). Therefore, the antioxidant effect of extracts or fractions of vegetables on animal products have not been well established when provided through the diet.…”
Section: Animal Productionmentioning
confidence: 99%